Ultra-sharp metal and nanotube-based probes for applications in scanning microscopy and neural recording - Borzenets, I. V. (American Institute of Physics, 2012)
This paper discusses several methods for manufacturing ultra-sharp probes, with applications geared toward, but not limited to, scanning microscopy (STM, AFM) and intra-cellular recordings of neural signals. We present recipes for making tungsten, platinum/iridium alloy, and nanotube fibril tips. Electrical isolation methods using Parylene-C or PMMA are described.